DIGITAL PUBLIC INFRASTRUCTURE AND CREDIT ACCESS FOR MICRO ENTERPRISES IN SOUTH ASIA - Dr.Padma Hazarika (EPRA International Journal of Economic and Business Review, 2026)
This paper provides an overview of how Digital Public Infrastructure has started to transform credit access for micro enterprises in South Asia. It describes how digital identity systems, real time payment platforms and associated registration databases can help to close information gaps between lenders and small businesses. Evidence synthesised from Indian registration platforms, Asian Development Bank assessments, and recent institutional literature consistently indicates that enterprises with verifiable digital footprints are more likely to secure formal credit. Meanwhile, the lack of infrastructure coverage, digital literacy and the continued need for collateral requirements continue to limit benefits for the smallest and most remote units. This paper also highlights the potential and the persistent limitations of relying on common digital systems to close the longstanding credit gap of micro enterprises.